A longitudinal investigation of gut microbiota dynamics in laying hens from birth to egg-laying stages - Seojin Choi; Eun Bae Kim (Animal Bioscience)
Objective Laying hens are a critical resource in global agriculture, valued for their egg production, which provides an economical and nutritious source of protein. This study aims to comprehensively characterize the developmental changes in the gut microbiota of Hy-Line Brown laying hens from birth to post-laying stages. Methods A total of 100 Hy-Line Brown laying hens were reared under controlled conditions, and feces and ileal contents were collected at three post-laying stages (151, 302, and 422 days). DNA was extracted from the samples and the V4 region of the 16S rRNA gene was sequenced using an Illumina MiSeq platform. The Random Forest algorithm was applied to identify microbial predictors and explore their relationships with age. Results The rapid increase in body weight continued until day 151, after which it stabilized through day 422. Fecal microbiome diversity increased until day 302, whereas in the ileal content, it grew until day 101 before declining. Throughout all stages, Firmicutes, Proteobacteria, and Bacteroidetes were the predominant phyla. Lactobacillus abundance peaked on day 10 (33.75%) across all sampling sites, whereas Escherichia-Shigella reached its maximum on day 21 but gradually diminished to 2.88% by day 422 (p<0.05). Machine learning analysis revealed that Candidatus Arthromitus and Clostridia vadinBB60 group consistently had the highest importance scores across all sample sites. At 302 day, body weight exhibited negative relationships with feces Brevibacterium (R = −0.87; p<0.05) and Brachybacterium (R = −0.79; p<0.05). Conclusion This study examined gut microbiota changes in Hy-Line Brown hens from birth to one-year post-laying, highlighting the impact of calcium-rich layer diets. The findings provide insights into microbiota dynamics and their relationship with age, which can be applied to optimize dietary strategies and improve laying hen productivity and health.